A randomized controlled trial comparing the effectiveness of individual versus household treatment for Scabies in Lambaréné, Gabon. - Julian Matthewman; Rella Zoleko Manego; Lia Betty Dimessa Mbadinga; Hana Šinkovec; Katrin Völker; Malik Akinosho; Christian Haedrich; Jeanne Tardif d'Hamonville; Bertrand Lell; Ayola Akim Adegnika; Michael Ramharter; Ghyslain Mombo-Ngoma (Public Library of Science (PLoS), 2020)
Background It is unclear whether individual treatment of scabies is similarly effective compared to household treatment. This study compared these two treatment strategies with topical benzyl benzoate for treating scabies in Lambaréné, Gabon. Methods Participants presenting with uncomplicated scabies were randomized into either the Individual Treatment group, where only the affected participants received treatment, or the Household Treatment group, where all family members were treated in parallel to the affected participants regardless of signs and symptoms. The primary endpoint was clinical cure after 28 days; the secondary endpoint was the proportion of affected household members per household after 28 days. Results After 28 days, from a total of 79 participants assessed, 67% (n = 53) were clinically cured; 59% (20/34) in the Individual Treatment group and 73% (33/45) in the Household Treatment group. Participants in the Household Treatment group had about twice the odds of being cured (odds ratio 1.9, 95% confidence interval: 0.8-4.9; p = 0.17). For the secondary outcome, an effect of similar size was observed. Conclusions Our findings show that treating close contacts of persons affected by scabies may be beneficial to patients and contacts, however, the benefit was less pronounced than anticipated and further research is needed to definitively answer this question.